Upakara Bali-based Electronic Student Worksheets on Geometry Topic for Second Grade of Elementary School - I Gusti Komang Agus Angga Putra Widiarta; I Made Suarjana; Basilius Redan Werang (Jurnal Ilmiah Sekolah Dasar, 2024)
The lack of contextualization and innovation in developing learning materials for 2nd-grade elementary school geometry has become a major issue leading to students' difficulty in understanding concepts. This research aims to develop an Electronic Student Worksheets Based on Ethnomathematics Upakara Bali in Geometry for 2nd-Grade Elementary School. Trial subjects in this study include two material experts, two media experts, one 2nd-grade teacher, 6 individual trial students, and 10 small group trial students. This research utilizes the ADDIE model (analyze, design, development, implementation, evaluation). Data collection methods used were questionnaires, interviews, and observations. Data analysis techniques involved quantitative and qualitative descriptive analyses. The results of this developmental research are the Electronic Student Worksheets product, covering: (a) the design and development of an ethnomathematics-based Electronic Student Worksheets on Upakara Bali for 2nd-grade Elementary School Geometry, including analysis, design, and development stages; (b) validity test results gain criteria of excellent qualification; (c) effectiveness test belongs to teacher response, individual trial score, small group trial score belongs to excellent qualification. Hence, it can be concluded that this Electronic Student Worksheets is suitable for use in the learning process. The implication of this research is the existence of a valid and suitable Electronic Student Worksheets to enhance 2nd-grade Elementary School geometry learning within the local cultural context.